Le projet pénitentiaire de Théodore Charpentier - Claire Illi (Criminocorpus)
This article intend to analyse a project for a prison realized in 1838, during the July Monarchy in France by the french architect Théodore Charpentier (1797-1867). Contributing to the european quest of an ideal prison, Charpentier observes the foreign architecture and proposes to the french society a model of prison which tries to satisfy the new penitentiary program : surveillance, isolation, work and amendment. The architect is convinced by the pennsylvanian regime of absolute reclusion which consequently determines the intern design of the prison. Full of philanthropic spirit and concerned about the well-being of his prisoners, Charpentier tries to make the reclusion of the delinquent comfortable and human in order to change the criminal so that he can return « reborn » to the society.